PENGENALAN KOMUNIKASI KRISIS PADA SISWA-SISWI SMK NEGERI 47 JAKARTA SELATAN - Dwi Kartikawati; Nurhasanah Nurhasanah; Purnomo Purnomo (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
The introduction to the fundamentals of crisis communication is an essential part of the education for Vocational Broadcasting students, considering their active role in the media and broadcasting sector. This program was conducted to equip students of SMK Negeri 47 Jakarta Selatan with basic crisis communication skills, aiming to prepare them to face future communication challenges at both personal and organizational levels. This community service activity targeted Broadcasting students and featured a crisis communication expert along with a practitioner from BRIN (Badan Riset dan Inovasi Nasional). The program included presentations, discussions, and Q&A sessions designed to enhance the students’ understanding and readiness in handling crises. As a result, the students demonstrated improved mental preparedness and the ability to maintain personal and institutional reputations in the digital era. Furthermore, this initiative lays the groundwork for ongoing crisis communication training programs at the school, providing valuable competencies for their future careers.